Produção de electricidade em Portugal - Pamplona, Raquel (2015)
In the present work we intend to do an analysis of the production of electricity in special regime in Portugal. We will focus in particular in the remuneration system through the feed-in tariffs. First, we will excurse throughout different legal diplomas that regulated the special regime in Portugal, exploring which guarantees were conferred to electricity generators throughout the years. We intend to also evaluate how the producers remunerative rights were (or not) protected in the various legislative changes. In the second part of the dissertation we will examine whether the feed-in tariffs may be considered as State aid. Due to the inclusion of the subject in EU Law, we will analyze EU regulation and case law to support our position about the Portuguese regime. Finally, and to the extent that the production of electricity in special regime has undergone several changes to its remunerative regime in the last few years, we propose to analyze more carefully the amendments in question. We will scrutinize the reasons that based the amendments in question, which are mainly based on the economic crisis suffered by the country. We will also examine how those changes may jeopardize the remunerative rights of the producers.